Gendered Political Violence as a Legal Framework: an analysis of the brazilian reality - Jacob Carneiro, Adriana; Jalalzai, Farida; A.G dos Santos, Pedro (Estudos Eleitorais, 2024)
In August of 2021, the Brazilian government sanctioned in the Electoral Code and the Penal Code the typification of violence against women in politics (VAWIP) as a punishable crime. This research provides a critical analysis of the implementation of the 2021 Law n. 14.192 that typifies VAWIP as a crime. To do so we discuss how the law addresses, in theory, the types of VAWIP identified in the extant literature (physical, psychological, sexual, economic, and semiotic). We then discuss Brazil’s VAWIP law contextualizing it within the Brazilian political landscape, regional (as well as global) perspectives on the issue, and comparing Brazil’s law with the Inter-American model law on the prevention, punishment, and eradication of violence against women in political life. We argue that Brazil’s VAWIP law provide the legal basis for addressing the issue, but the ambiguous and broad language used in the law leaves a lot of room for interpretation of what will typify this kind of violence.